Cobalt Diazo-Compounds: From Nitrilimide to Isocyanoamide via a Diazomethanediide Fleeting Intermediate - Aghazada, Sadig; Fehn, Dominik; Heinemann, Frank Wilhelm; Munz, Dominik; Meyer, Karsten (Angewandte Chemie International Edition, 2021)
Lithium trimethylsilyldiazomethanide and a cobalt (II) precursor with an N-anchored tris-NHC (TIMENmes) ligand provide access to the cobalt nitrilimide 1. Complex 1 was structurally characterized by single-crystal X-ray diffractometry (SC-XRD) and its electronic structure was examined in detail, including EPR spectroscopy, SQUID magnetometry and computational analyses. The desilylation of the C-(trimethylsilyl)nitrilimide reveals a transient complex with an elusive diazomethanediide ligand, which substitutes one of the mesitylene rings of the ancillary ligand through C-N bond cleavage. This transformation results in the cyclometalated cobalt(II) complex 2, featuring a rare isocyanoamido-kappa-C ligand.
CRIS-Team WoS Importer:2021-04-16